2013
DOI: 10.11648/j.sjcm.20130203.20
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer′s Disease and Type 2 Diabetes Mellitus: Risk Factors and Effectiveness of Antidiabetic Agents in Treatment of Alzheimer′s Disease

Abstract: The aim of this review is to highlight the association between type 2 diabetes mellitus (DM) and cognitive impairment/Alzheimer's disease (AD) and provide an updated summary of the evidence related to various potentially modifiable risk factors such as hyperinsulinaemia,insulin resistance,hypo-and hyperglycaemia, vascular risk factors like hypertension and obesity, micro and macrovascular complications, depression in AD.Treating modifiable risk factors can reduce the prevalence of AD.In addition we provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Similarly, non-black participants with memory complaints but without diabetes had over two-fold increased risk of dementia, while non-black participants with memory complaints but with diabetes had no increased risk. Although it has been shown that diabetes increases the risk of cerebrovascular pathology rather than Alzheimer’s disease pathology [29], use of hypoglycemic medications may decrease the risk of dementia [27], but the effects of different antidiabetic drugs may vary [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, non-black participants with memory complaints but without diabetes had over two-fold increased risk of dementia, while non-black participants with memory complaints but with diabetes had no increased risk. Although it has been shown that diabetes increases the risk of cerebrovascular pathology rather than Alzheimer’s disease pathology [29], use of hypoglycemic medications may decrease the risk of dementia [27], but the effects of different antidiabetic drugs may vary [28]. …”
Section: Discussionmentioning
confidence: 99%